Physiological aspects of imprinting and homing migration in salmon emerging research and opportunities - Ueda, Hiroshi, 1951- (Advances in environmental engineering and green technologies (AEEGT) book series., 2020)
"This book examines the physiological mechanisms of natal stream imprinting and homing in salmon with special references to hormone, olfaction, memory, and behavior"--